Deoxygenation of algae oil over nickel-based nanoparticles supported on zeolite Y / Choo Min Yee - Choo , Min Yee (2021)
Biofuel has gained more attention worldwide due to the depletion and environmental issue of fossil fuel especially the carbon dioxide emission. Biofuel offers an effective carbon offset due to the modern carbon cycle. The high lipid productivity and tolerance towards ecological stress has make microalgae a promising feedstock for biofuel production. Conventional biofuel or known as biodiesel is used as after blended with petroleum fuel (diesel). Deoxygenation is a viable process to produce green biofuel, which shares the similar properties as petroleum fuel. Typically, deoxygenation is performed under high hydrogen gas (H2) pressure conditions with the use of expensive precious metal-supported catalysts. Therefore, this study aims to utilize zeolite Y based catalyst with transition metals catalyst for production of green biofuel via deoxygenation in solvent-free and hydrogen-free condition. Zeolite Y, a widely used catalyst in the industry and scientific community due to its large micropore opening (7.3 × 7.3 Å2) was selected as the support. Then, the selection of suitable TMO supported on commercial microporous zeolite Y. NiO showed the best deoxygenation ability (76.2% triolein conversion, 84.3% hydrocarbon selectivity, initial rate of 8.2 goilh-1) at 380 oC within 2 h. However, microporous zeolite Y with limited external surface area (<30 m2/g) faces diffusional limitation. This drawback renders it not ideal for the reactions involving bulky reactants such as triolein (0.625 × 4.37 nm). Therefore, introduction of mesoporosity was achieved by synthesizing nanosized zeolite Y is under organotemplate-free approach. The unsupported nanosized zeolite Y65 (crystal size: 65 nm) exbibited large external surface area (62 m2/g) and intercrystal mesoporosity. It showed 65.2% triolein conversion with 69.2% hydrocarbon selectivity at 380 oC within 4 h. Two preparation methods, namely impregnation (IM) and deposition-precipitation (DP) were investigated for preparation of NiO supported on nanosized zeolite Y (Y65). The DP-Y65 showed the best performance due to the small NiO nanoparticle (3.57 nm), high hierarchical factor (H.F) of 0.084, and high Brønsted to Lewis (B/L) ratio (0.29). The triolein conversion and hydrocarbon selectivity of 80.0% and 90.3% was achieved at 380 oC within 1 h. The initial rate of DP (14.8 goilh-1) was 1.5 times higher than that of IM (9.6 goilh-1). However, the DP-Y65 showed the sign of deactivation with deposition of filamentous carbon due to the reduced mesoporosity after the NiO loading. Finally, hierarchical zeolite Y with uniform mesopore (5.8 nm) was synthesized with addition of amphiphilic organosilane (TPOAC). After that, NiO with different Ni loading was deposited on hierarchical zeolite Y via DP method. It was found that 10 wt% of NiO with coexistence of 1:1 phyllosilicate (PS) deposited on hierarchical zeolite Y (10Ni-MY0.15) showed the best deoxygenation performance. The algae oil conversion of 87.2%, hydrocarbon selectivity of 98.8%, and initial rate of 16.0 goilh-1 was achieved at 380 oC within 1 h. Surprisingly, the 10Ni-MY0.15 showed good recyclability without filamentous carbon formation, offering it as a promising deoxygenation catalyst in producing green biofuel.